2023
DOI: 10.1038/s41598-023-30021-3
|View full text |Cite
|
Sign up to set email alerts
|

Rice-memolin, a novel peptide derived from rice bran, improves cognitive function after oral administration in mice

Abstract: Many people eat polished rice, while rice bran, a by-product known to be rich in protein and expected to have potential functions for health benefits, has not been effectively utilized. In this study, we determined that orally administered Val-Tyr-Thr-Pro-Gly (VYTPG) derived from rice bran protein improved cognitive decline in mice fed a high-fat diet (HFD). It was demonstrated that VYTPG was released from model peptides corresponding to fragment sequences of original rice proteins (Os01g0941500, Os01g0872700,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…It has been reported that diabetic patients are 1.7 times more susceptible to dementia than the control group 2 . Furthermore, we revealed that a high‐fat diet (HFD) induces glucose metabolism impairment and cognitive decline in mice 3,4 . Considering that milk intake is a protective factor, we found that tripeptide derived from α casein, a major component in bovine milk, ameliorated cognitive decline induced by HFD intake 3 .…”
Section: Introductionmentioning
confidence: 74%
See 4 more Smart Citations
“…It has been reported that diabetic patients are 1.7 times more susceptible to dementia than the control group 2 . Furthermore, we revealed that a high‐fat diet (HFD) induces glucose metabolism impairment and cognitive decline in mice 3,4 . Considering that milk intake is a protective factor, we found that tripeptide derived from α casein, a major component in bovine milk, ameliorated cognitive decline induced by HFD intake 3 .…”
Section: Introductionmentioning
confidence: 74%
“…We previously reported that milk‐derived YLG used to improve cognitive decline induced by HFD intake increased insulin sensitivity in the ITT 3 . VYTPG, named rice‐memolin, also improved glucose metabolism after oral administration 4 . In contrast, OMA improved cognitive function but did not affect blood glucose levels in the OGTT and ITT (Figure S4).…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations